2011
DOI: 10.1051/0004-6361/201117081
|View full text |Cite
|
Sign up to set email alerts
|

WASP-43b: the closest-orbiting hot Jupiter

Abstract: We report the discovery of WASP-43b, a hot Jupiter transiting a K7V star every 0.81 d. At 0.6-M the host star has the lowest mass of any star currently known to host a hot Jupiter. It also shows a 15.6-d rotation period. The planet has a mass of 1.8 M Jup , a radius of 0.9 R Jup , and with a semi-major axis of only 0.014 AU has the smallest orbital distance of any known hot Jupiter. The discovery of such a planet around a K7V star shows that planets with apparently short remaining lifetimes owing to tidal deca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
153
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 42 publications
13
153
1
Order By: Relevance
“…Radial velocity and photometric data are available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/551/A80 WASP is the first gas giant around a δ Scuti ) and the population of very short period gas giants, such as WASP-12, 18, 19, and43 (Hebb et al 2009, 2010;Hellier et al 2009Hellier et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Radial velocity and photometric data are available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/551/A80 WASP is the first gas giant around a δ Scuti ) and the population of very short period gas giants, such as WASP-12, 18, 19, and43 (Hebb et al 2009, 2010;Hellier et al 2009Hellier et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting case is the WASP-43 system, consisting of a low-mass K7V-type host star and the hot Jovian planet WASP-43 b (Hellier et al 2011). Today, only a single hot Jupiter is known to orbit an even less massive star, namely, the 0.59 M M-star KOI-254 (Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, with a semi-major axis of 0.015 AU, WASP-43 b remains the most closely orbiting hot Jupiter known 1 . WASP-43 b has a circular orbit and transits its host star every 0.81 d (Hellier et al 2011;Gillon et al 2012). With about the same size as Jupiter and twice its mass, it also shows twice the mean Jovian density (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the host star's cool temperature and small radius, as well as a small semimajor axis, the system produces deep eclipses both in transit and occultation, making WASP-43b one of the most observed and studied exoplanets today. Multiple photometric and spectroscopic observations of WASP-43b (Hellier et al 2011;Gillon et al 2012;Wang et al 2013;Blecic et al 2014;Chen et al 2014;Stevenson et al 2014b;Zhou et al 2014) revealed no thermal inversion in the planetary atmosphere, low day-night energy redistribution, water abundance 1-10× solar, and a slightly enhanced C/O ratio compared to solar (Benneke 2015;J. Blecic et al 2016).…”
Section: Background Of the Models Usedmentioning
confidence: 99%